Hadith #534 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
I was with the Messenger of Allah (ﷺ) one night. He came down (from the ride) and relieved himself. He then came and I poured water upon him from the jar that I carried with me. He performed ablution and wiped over his socks.
Grade: Sahih

Hadith #535 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
I was in the company of the Messenger of Allah (ﷺ) on a journey when he said: Mughira take hold of this jar (of water). I took hold of it and I went out with him. (I stopped but) the Messenger of Allah (ﷺ) proceeded on till he was out of my sight. He relieved himself and then came back and he was wearing a tight-sleeved Syrian gown. He tried to get his forearms out. but the sleeve of the gown was very narrow, so he brought his hands out from under the gown. I poured water over (his hands) an
Grade: Sahih

Hadith #536 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
The Messenger of Allah (ﷺ) went out for relieving himself. When he came back I brought for him a jar (of water) and poured water upon his hands and He washed his face. He tried to wash his forearms, but as the (sleeves of the) gown were tight. He, therefore, brought them out from under the gown. He then washed them, wiped his head, and wiped his socks and then prayed.
Grade: Sahih

Hadith #854 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
I also moved along with him till he came to the people and (he found) that they had been saying their prayer under the Imamah of ‘Abd al-Rahman b. ‘Auf. The Messenger of Allah (ﷺ) could get one rak ah out of two and said (this) last rak’ah along with the people. When Abd al-Rahman b. ‘Auf pronounced the salutation, the Messenger of Allah (ﷺ) got up to complete the prayer. This made the Muslims terrified and most of them began to recite the glory of the Lord. When the Messenger of All
Grade: Sahih

Hadith #1237 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
When the Messenger of Allah (ﷺ) finished the prayer and pronounced salutation he uttered (this supplication):” There is no god but Allah. He is alone, Who has no partner. To Him belongs the sovereignty and to Him praise is due and He is Potent over every. thing. O Allah! no one can withhold what Thou givest, or give what Thou withholdest, and the riches cannot avail a wealthy person with Thee.”
Grade: Sahih

Hadith #3637 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
If I were to see a man with my wife, I would have struck him with the sword, and not with the flat part (side) of it. When Allah’s Messenger (ﷺ) heard of that, he said: Are you surprised at Sa’d’s jealousy of his honour? By Allah, I am more jealous of my honour than he, and Allah is more jealous than I. Because of His jealousy Allah has prohibited abomination, both open and secret And no person is more jealous of his honour than Allah, and no persons, is more fond of accepting an excuse
Grade: Sahih

Hadith #4263 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
Should we pay indemnity for one who, neither ate, nor drank, nor made any noise, who was just like a nonentity? Thereupon Allah’s Messenger (ﷺ) remarked: He speaks rhymed phrases like the people of the desert. He did impose indemnity upon them.
Grade: Sahih

Hadith #4264 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
A woman killed her fellow-wife with a tent-pole. Her case was brought to Allah’s Messenger (ﷺ), and he gave judgment that blood-wit should be paid by the relatives (of the offender) on the father’s side. And as she was pregnant, he decided regarding her unborn child that a male or a female slave of good quality be given. Some of her offender’s) relatives said: Should we make compensation for one who never ate, nor drank, nor made any noise, who was like a nonentity? Thereupon Allah’s M
Grade: Sahih

Hadith #4353 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
Verity Allah, the Glorious and Majestic, has forbidden for you: disobedience to mothers, and burying alive daughters, withholding the right of others in spite of having the power to return that to them and demanding that (which is not one’s legitimate right). And He disapproved three things for you; irrelevant talk, persistent questioning and wasting of wealth.
Grade: Sahih

Hadith #5452 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
When I came to Najran, they (the Christians of Najran) asked me: You read” O sister of Harun” (i. e. Hadrat Maryam) in the Qur’an, whereas Moses was born much before Jesus. When I came back to Allah’s Messenger (ﷺ) I asked him about that, whereupon he said: The (people of the old age) used to give names (to their persons) after the names of Apostles and pious persons who had gone before them.
Grade: Sahih

Hadith #5478 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
O, myson, why are you worried because of him? He will not harm you. I said: The people think that he would have with him rivers of water and mountains of bread, whereupon he said: He would be more insignificant in the sight of Allah than all these things (belonging to him).
Grade: Sahih

Hadith #6947 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
(Why do you undergo so much hardship despite the fact that) Allah has pardoned for you your earlier and later sins? Thereupon he said: May I not (prove myself) to be a grateful servant (of Allah)?
Grade: Sahih

Hadith #7194 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
No one asked Allah’s Messenger (ﷺ) more about Dajjil than I asked him. He said: He should not be a source of worry to you for he would not be able to do any harm to you. I said: Allah’s Messenger, it is alleged that he would have along with him (abundance of) food and water. Thereupon he said: He would be very insignificant in the eye of Allah (even) with all this.
Grade: Sahih

Hadith #7195 - Sahih Muslim - al-Mughira ibn Shu'ba (Sahih Muslim)
What did you ask? Mughira replied: I said that the people alleged that he would have a mountain load of bread and mutton and rivers of water. Thereupon he said: He would be more insignificant in the eye of Allah compared with all this.
Grade: Sahih